INDICATORS OF OXIDATIVE-NITROSATIVE STRESS IN PERIODONTAL TISSUES OF RATS EXPOSED TO LOCAL IRRITATION OF GUMS DURING LIPOPOLYSACCHARIDE-INDUCED SYSTEMIC INFLAMMATORY RESPONSE - Yelinska, A.M.; Kostenko, V.O. (World of Medicine and Biology, 2019)
The study carried out on 40 white rats was aimed at assessing the indices of oxidative-nitrosatitistic stress in periodontal tissues under the condition of combined effect of both local and systemic factors. Local irritation of the gums was induced by the local pathogenic factor (5% sodium hydroxide solution) during the simulation of systemic inflammatory response (SIR) induced by intraperitoneal administration of lipopolysaccharide Salmonella typhi (pyrogenalum) in a dose of 0.4 μg/kg of weight 3 times during the first week, and once a week for the following 7 weeks. It has been shown that simulation of SIR is accompanied by an increase in the production of superoxide anion-radical (.О ) in periodontal tissues, by the dysregulation of the nitrogen oxide cycle with the simultaneous activation of its NO-synthase (NOS) and nitrate / nitrite reductase components, as well as by the increase in peroxinitrite ion concentration. The application of alkali onto the gum increases the .О production and the activity of NOS without disturbing the functioning of the nitric oxide (NO) cycle and increasing in the peroxynitrite ion content in the tissues. The application of 5% sodium hydroxide solution onto the gums against the background of SIR results in an increase in .О generation by NADH- and NADPH-dependent sources in periodontal tissues, the dysregulation of the NO cycle with the increase in peroxinitrite ion concentration that exceeds relevant indices obtained at separate action of these systemic and local factors.